New Quality Productive Forces Empowering Innovation in China’s Pharmaceutical Manufacturing Industry: Pathways toward High-Quality Development - Li, Han; Jin, Ziyue; Liu, Ronghe; Dong, Yueting; Wang, Dicheng (Asia Pacific Economic and Management Review, 2026)
This study examines the impact of new-quality productive forces (NQPF) on the innovation performance of China’s pharmaceutical manufacturing enterprises and explores its internal mechanisms. Using panel data of A-share listed pharmaceutical firms from 2015 to 2023, a fixed-effects model is constructed, with instrumental variable (IV) and system GMM estimations applied to address endogeneity. The empirical results show that NQPF significantly enhance firms’ innovation performance, and the findings remain robust under multiple model specifications. Mechanism analysis further reveals that NQPF promote innovation both directly and indirectly by improving technological stability and technological diversification. These results indicate that NQPF strengthen the depth of technological accumulation while expanding the breadth of innovation exploration. From a policy perspective, fostering NQPF should be prioritized to upgrade China’s pharmaceutical industry. Governments should enhance innovation policy frameworks and digital infrastructure, while firms should advance intelligent transformation and data-driven innovation management to achieve high-quality and sustainable development.